DAYA TARIK PENGGUNAAN MEME DAN DAYA TARIK KONTEN INFORMATIF PADA INSTAGRAM NETFLIX INDONESIA (@NETFLIXID) TERHADAP KEPUTUSAN PEMBELIAN LAYANAN VIDEO ON DEMAND NETFLIX - Iffah Shofiyah Ariefah; Lintang Ratri Rahmiaji; Nurist Surayya Ulfa (Interaksi Online, 2023)
Netflix is the first SVOD company to expand its wings in the Indonesian market. However, currently Netflix's ratings have fluctuated from Q4 2019 to 2022. In 2022, Netflix experienced a drastic decline compared to the previous year. Therefore, Netflix Indonesia launched its marketing strategy, one of which is through social media content, especially Instagram. This study aims to determine the effect of the attractiveness of using memes and the attractiveness of informative content on Instagram Netflix Indonesia (@netflixid) on purchasing decisions for Netflix's video-on-demand service. This study uses the Attribution Theory, with a research sample of 100 respondents with female and male characteristics, aged 18-36 years who follow or follow the Netflix Indonesia Instagram account (@netflixid) and are aware of Netflix Indonesia's Instagram posts. Testing and data analysis in this study using multiple linear regression analysis. The results of the f-test show that the attractiveness of using memes (X1) and the attractiveness of informative content (X2) on Instagram Netflix Indonesia (@netlfixid) have an effect on the decision to purchase Netflix's video-on-demand service (Y), this is in line with the Attribution theory which explains how an individual's perception of a stimulus can influence his actions. However, the magnitude of the influence given is 14.2% where this data means that there are other possible variables that can influence the decision to buy Netflix's video-on-demand service. This is further corroborated by the results of the T-test which shows that if the single variable test, namely the use of attractiveness on Instagram Netflix Indonesia, has no effect on the purchase decision of Netflix's video-on-demand service. Meanwhile, the attractiveness variable for informative content has an influence on the decision to purchase Netflix's video-on-demand service. Based on the research results, Netflix Indonesia can continue to optimize its informative content production, and for further research, it can examine other variables that are assumed to influence the decision to purchase Netflix's video-on-demand service.